THE USE OF INDIRECTNESS AND TAG QUESTIONS BY POWERFUL AND FOWERLESS MEN AND WOMEN ON TRIALS: EVIDENCE FROM INDONESIA - EUIS RINA MULYANI (State University of Medan, 2021)
This study was aimed at investigating the use of indirectness and question tags in some Indonesian trials. The data were chosen randomly from YouTube’s videos. The subjects were twenty people consisting of judges, witnesses, and defendants (the accused). To analyze the data, the conversations of the videos were firstly transcribed verbatim. Then, they were analyzed using the framework of Thomas (1995) and Holmes (1984). The data showed that indirect speech style and question tags were more attached to powerful women.